Overexpression of a Tartary Buckwheat Gene, FtbHLH3, Enhances Drought/Oxidative Stress Tolerance in Transgenic Arabidopsis - Yao, Pan-Feng; Li, Cheng-Lei; Zhao, Xue-Rong; Li, Mao-Fei; Zhao, Hai-Xia; Guo, Jin-Ya; Cai, Yi; Chen, Hui; Wu, Qi (Frontiers in Plant Science, 2017)
bHLH (basic helix-loop-helix) transcription factors play important roles in the abiotic stress response in plants, but their characteristics and functions in tartary buckwheat (Fagopyrum tataricum), a flavonoid-rich cereal crop with a strong stress tolerance, have not been fully investigated. Here, a novel bHLH gene, designated FtbHLH3, was isolated and characterized. Expression analysis in tartary buckwheat revealed that FtbHLH3 was mainly induced by polyethylene glycol 6000 (PEG6000) and abscisic acid (ABA) treatments. Subcellular localization and a yeast one-hybrid assay indicated that FtbHLH3 has transcriptional activation activities. Overexpression of FtbHLH3 in Arabidopsis thaliana resulted in increased drought/oxidative tolerance, which was attributed to not only lower malondialdehyde (MDA), ion leakage (IL) and reactive oxygen species (ROS) but also higher proline (Pro) content, activities of antioxidant enzymes, and photosynthetic efficiency in transgenic lines compared to wild type (WT). Moreover, qRT-PCR analysis indicated that the expression of multiple stress-responsive genes in the transgenic lines was significantly higher than in WT under drought stress. In particular, the expression of AtNCED, a rate-limiting enzyme gene in ABA biosynthesis, was increased significantly under both normal and stress conditions. Additionally, an ABA-response-element (ABRE) was also found in the promoter regions. Furthermore, the transgenic Arabidopsis line of the FtbHLH3 promoter had higher GUS activity after drought stress. In summary, our results indicated that FtbHLH3 may function as a positive regulator of drought/oxidative stress tolerance in transgenic Arabidopsis through an ABA-dependent pathway.